Vitamin D deficiency and depression in obese adults: a comparative observational study - Leila Kamalzadeh (BMC, 2021)
Abstract Background Amongst the contributing factors of depression, vitamin D deficiency has increasingly drawn attention in recent years. This paper seeks to examine the association between serum vitamin D level and depression in patients with obesity. Methods In this comparative observational study, serum 25-hydroxyvitamin D [25(OH)D] levels were compared between obese individuals with depression (n = 174) and those without depression considering the effect of potential confounders. Participants were selected from males and females aged 18 to 60 years old visiting the outpatient obesity clinic of Rasoul-e Akram hospital, Tehran, Iran. The diagnosis of depressive disorder was made based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria. Additional clinical and laboratory data were collected from hospital electronic records. Mann–Whitney U test (nonparametric), Student’s t-test (parametric), and Chi-squared test were used to analyze the differences between the two groups. To examine age and gender differences in the relationship between vitamin D deficiency and depression, stratified analyses were conducted by age and gender groups. Results The mean 25(OH) D levels were significantly different between depressed and non-depressed groups (20 ± 15 vs. 27 ± 13, P <  0.001). Vitamin D insufficiency/deficiency was detected in 78 and 67% of the depressed and non-depressed groups, respectively, which was significantly different (P = 0.03). The associations between depression and the serum 25(OH) D levels were observed regardless of gender and age. The overall average vitamin D levels were not significantly different between total males and females (22 ± 13 vs. 23 ± 14, P = 0.49). The average level of vitamin D was higher in the older age group (40–60 years) compared to younger participants (18–39 years) (26 ± 15 vs. 21 ± 13, P = 0.004). Conclusion The present study provides additional evidence for the hypothesis that low vitamin D serum concentration is associated with depression in obese adults, and highlights the need for further research to determine whether this association is causal.